Acute appendicitis – a study with special reference to diagnostics, severity assessment and association with appendiceal neoplasms - Lietzén, Elina (My University, 2019)
Acute appendicitis is the most common indication for emergency abdominal surgery. Today, it is generally accepted that acute appendicitis does not invariably progress to perforation. Recent studies have shown that the majority of uncomplicated infections will subside with antibiotics alone. To optimize the treatment for acute appendicitis, accurate diagnostic tools such as computed tomography (CT) are required. As the treatment of uncomplicated acute appendicitis may be changing towards conservative treatment, there has been a rising concern of missing possible appendiceal tumors, found in 0.7-1.7% of appendectomy specimens. This study was carried out to evaluate the feasibility of clinical history and clinical and laboratory findings in diagnosing acute appendicitis as well as in the differential diagnosis between uncomplicated and complicated acute appendicitis. This study also aimed to assess the accuracy of CT and the role of the experience of the radiologist in the emergency setting in the diagnosis of acute appendicitis. In addition, this study was performed to assess both the incidence of appendiceal tumors among acute appendicitis patients and the possible tumor association with acute appendiceal inflammation. Both clinical findings and laboratory tests were unable to reliably diagnose acute appendicitis or to assess the severity of inflammation. Contrast enhanced abdominal CT displayed high sensitivity and specificity in diagnosing suspected acute appendicitis and in the differential diagnosis of assessing its severity. The experience of the radiologist did not affect the diagnostic accuracy. The incidence of appendiceal tumors among acute appendicitis was very low but there was a statistically significantly higher tumor risk associated with complicated acute appendicitis. Appendiceal tumors were rarely detected in preoperative imaging and even more rarely in the early stage of the disease. Thus, there is a low risk of missing possible appendiceal tumors related to the nonoperative treatment of uncomplicated acute appendicitis.

Akuutti umpilisäketulehdus – tutkimuksia diagnostiikasta, vaikeusasteen määrityksestä ja yhteydestä umpilisäkkeen kasvaimiin Akuutti umpilisäketulehdus on yksi yleisimmistä päivystysleikkauksen aiheista. Nykytiedon mukaan umpilisäkkeen tulehdus ei aina johda umpilisäkkeen puhkeamiseen. Viimeaikaisten tutkimusten mukaan iso osa komplisoitumattomista eli lievemmistä akuuteista umpilisäketulehduksista voitaisiin hoitaa yksinomaan antibiooteilla. Optimaalisen hoidon valinnan edellytyksenä on tarkka diagnoosi, johon tarvitaan tietokonetomografiakuvantamista (TT). Komplisoitumattoman umpilisäketulehduksen konservatiivista hoitoa arvioitaessa on otettava huomioon, että osalla umpilisäketulehduspotilaista voidaan todeta poistetussa umpilisäkkeessä sattumalöydöksenä kasvain, esiintyvyys 0.7-1.7 %. Tämän väitöskirjatyön tarkoituksena oli selvittää kliinisen diagnostiikan osuvuutta sekä umpilisäketulehduksessa että erotusdiagnostiikassa komplisoituneen ja komplisoitumattoman tulehduksen välillä. Tutkimme myös TT:n osuvuutta ja radiologin kokemuksen merkitystä umpilisäketulehduksen diagnostiikassa. Tutkimuksen tarkoituksena oli lisäksi selvittää umpilisäkkeen kasvainten esiintyvyyttä akuutin umpilisäketulehduksen vuoksi leikatuilla sekä kasvainten mahdollista yhteyttä umpilisäkkeen tulehdukseen. Akuutin umpilisäketulehduksen diagnosoiminen ja tulehduksen vaikeusasteen määritys kliinisten oireiden ja löydösten sekä laboratoriotutkimusten avulla osoittautui epävarmaksi. Varjoainetehosteisella TT-tutkimuksella saavutettiin erinomainen diagnostinen tarkkuus riippumatta radiologin kokemuksesta. Sen sijaan umpilisäkkeen kasvaimet löytyivät kuvantamisella vain harvoin varsinkin taudin alkuvaiheessa. Umpilisäkkeen kasvainten esiintyvyys akuutin umpilisäketulehduksen yhteydessä oli erittäin pieni. Kasvaimen riski oli tilastollisesti merkittävästi suurempi komplisoituneissa akuuteissa umpilisäketulehduksissa. Vaikka komplisoitumattoman akuutin umpilisäketulehduksen konservatiivinen hoito tulevaisuudessa yleistyisi, on umpilisäkkeen kasvaimen hoitamatta jäämisen riski hyvin vähäinen.